Purposes and restrictions for transparency in the Paris Agreement era of the climate regime : A content analysis of Parties’ submissions in the negotiations on the implementation guidelines for the transparency framework under the Paris Agreement - Leino, Marianne (fi=Turun yliopisto|en=University of Turku|, 2018)
The thesis offers an inquiry to the international climate negotiations on the implementation guidelines for the transparency framework under the Paris Agreement. The goal is to shed light on the purposes, principles and restrictions parties attach to transparency and how their views on purposes, principles and restrictions converge or diverge. While regime theory provides the underlying theoretical framework for the study, a variety of transparency literature is covered in order to better understand the term ‘transparency’. The analysis aims to increase the understanding of ‘transparency’ as a concept, and to place the conceptualization of ‘transparency’ under the Paris Agreement in the context of a wider transparency discussion. The analysis relies on qualitative content analysis. Parties’ submissions in the negotiations under the Ad Hoc Working Group on the Paris Agreement 2016-2017 serve as the research material for the analysis. Main findings conclude that purposes of transparency are widely shared among the countries. Divergences occur mostly in Parties’ views on principles and restrictions for transparency framework. The old disputes, such as differentiation, keep on emerging as the Paris Agreement left the operationalization of the transparency framework and its principles to be agreed in December 2018.